1965
DOI: 10.1002/pssb.19650080324
|View full text |Cite
|
Sign up to set email alerts
|

Die Erholung des elektrischen Widerstandes in abgeschrecktem Kupfer

Abstract: Es wird das Ausheilen des elektrischen Widerstandes in abgeschrecktem Kupfer untersucht, wobei je eine Erholungsstufe im Bereich 0 bis 100 °C und 100 bis 200 °C gefunden wird. Die obere Stufe wird durch die Wanderung der Einfachleerstellen erklärt, wobei sich (in Einklang mit Selbstdiffusions‐ und Hochtemperaturdaten) als Aktivierungsenergie der Wanderung W1 = 1,06 eV ergibt. Die untere Stufe kann als Ausheilen von Doppelleerstellen, die mit Einfachleerstellen im lokalen Gleichgewicht stehen, gedeutet werden. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

1965
1965
2012
2012

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 36 publications
0
6
0
2
Order By: Relevance
“…We shall first discuss three attempts to deduce EFv from quenching experi- Since the reaction order for this process has not been determined, nothing conclusive may be said about E Y V . The temperature range is the same as that studied in the above-mentioned experiments of Ramsteiner et al [44], and it is indeed likely that the same process has been investigated in both papers [42,44].…”
Section: Monovacancy Propertiesmentioning
confidence: 99%
“…We shall first discuss three attempts to deduce EFv from quenching experi- Since the reaction order for this process has not been determined, nothing conclusive may be said about E Y V . The temperature range is the same as that studied in the above-mentioned experiments of Ramsteiner et al [44], and it is indeed likely that the same process has been investigated in both papers [42,44].…”
Section: Monovacancy Propertiesmentioning
confidence: 99%
“…[27,28] All anneal out by rapid room-temperature or near-room-temperature diffusion. Of particular interest here, Pickering and Wagner [1] calculated the diffusivity of quenched-in divacancies in copper as 1.3 ϫ 10 Ϫ12 cm 2 /s from the resistivity measurements of Ramsteiner et al [29] -remarkably close to the maximum values reported in Figure 12 for Ag diffusivities in Cu. Returning to the issue of SCC, which motivated the present investigation, Aaltonen et al [7] calculated diffusivities of 10 Ϫ13 to 10 Ϫ10 cm 2 /s as necessary to sustain the crack-advance increments measured by Beggs et al [30] in brass and stainless steel.…”
Section: Data Analysis and Discussionmentioning
confidence: 81%
“…Since some curvature is indicated in the data plotted either way, this indicates that the process would be best considered as one with a variable activation energy. The measured activation energy of (1.1 & 0.1) eV which is associated with the temperature range around 200 "C, corresponds to the second stage of annealing in quenched copper, as measured by resistivity changes [21], and is, accordingly, assigned to single vacancy motion.…”
Section: Isothermal Studies Between 190 and 300 O Cmentioning
confidence: 99%